ANALISIS STRATEGI E-PROMOTION JASA MAKE-UP ARTIST MELALUI INSTGRAM (Studi Pada Chels Makeup artist di Bandar Lampung) - Damayanti Damayanti; Suprihatin Ali; Mediya Destaia (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2018)
This study aims to analyze the e-promotion strategy carried out by chels.makeupartist through instragam. . The research method that used is qualitative research with content analysis approach model and the main data source in this study is Instagram. The findings in this study are the promotional strategies conducted by chels.makeupartist are social media strategies, especially Instagram. In this social media strategy it contains advertising, publicity and sales promotions for either the services or goods offered. The promotion is done by displaying the portfolio of services that have been done on the Instagram account they have.